Porous Ag/polymer composite microspheres for adsorption and catalytic degradation of organic dyes in aqueous solutions. (11th February 2015) - Yang, Yu; Liao, Huiling; Tong, Zhen; Wang, Chaoyang
Abstract: Porous poly(styrene–divinyl benzene) (marked as PSD) microspheres with interconnected structure were facilely achieved by a suspension polymerization based on water-in-oil-in-water emulsion templates. The internal water-in-oil emulsion is a type of high internal phase emulsion, making it possible to fabricate porous open-cell microspheres. Furthermore, ascribe to the high concentration (much larger than critical micelle concentration) of hydrophobic surfactant in the oil phase, large amount of reverse micelles were generated and much more controllable and accessible pore structures of PSD microspheres were fabricated. Subsequently, sulfonated PSD microspheres and Ag-loading PSD hybrid microspheres were successfully achieved based on the above PSD microspheres. It was demonstrated that the sulfonated PSD microspheres could effectively adsorb dyes in an aqueous solution, and that the Ag-loading hybrid microspheres exhibited excellent catalytic degradation of the dyes. We believe our functional porous microspheres could be potential candidates as pollutant adsorbents, enzyme immobilization, and catalyst carriers.